Understanding Enamel Defects: Causes, Diagnosis, And Treatment Strategies (Journal of Namibian Studies : History Politics Culture, 2023)
Dental enamel defects pose significant challenges to oral health and aesthetics, affecting individuals of all ages. Among these defects, Amelogenesis Imperfecta (AI) and Dentinogenesis Imperfecta (DI) stand out as rare genetic disorders impacting enamel and dentin formation, respectively. AI manifests in various forms, leading to discolored, pitted, or malformed enamel, while DI primarily affects dentin, resulting in weakened tooth structure and increased susceptibility to fractures. Understanding the causes, symptoms, and treatment options for AI and DI is crucial for effective management. This abstract provides an overview of these conditions, highlighting genetic and environmental factors contributing to their development. Key diagnostic methods, including dental examination and genetic testing, are discussed, along with treatment strategies such as bonding, crowns, and orthodontic interventions. By addressing these defects comprehensively, individuals with AI and DI can achieve improved dental health and quality of life.